A new water-soluble polymer fluorescent chemosensor with thiophene Schiff base site for selectively sensing Al3+ ions. (22nd January 2021) - Xu, Yuhang; Kong, Liuqi; Bai, Liping; Chen, Amin; Li, Na; Cheng, Lijuan; Liu, Wenjie; Sun, Xiaoqing; Tao, Farong; Wang, Liping; Li, Guang
Abstract: A new thiophene Schiff base-based fluorescent "turn-on" chemosensor PEGSB was developed to efficiently detect Al 3+ in water. PEGSB exhibited highly selective and sensitive fluorescence response toward Al 3+ even in the presence of other competitive metal ions. The detection limit of PEGSB was calculated to be 1.32 × 10 −8  M. The binding stoichiometry of PEGSB-Al 3+ was found to be 1:1 by Job's plot analysis. PEGSB showed excellently sensing capability towards Al 3+ in a wide pH range from 5 to 9. In addition, PEGSB displayed a better reversibility for Al 3+ detection with the aid of EDTA. An INHIBIT logic gate was constructed by using Al 3+ and EDTA as input signals and the fluorescence intensity at 444 nm as output signal. Furthermore, test papers containing PEGSB were fabricated for convenient and rapid detection of Al 3+ in real water samples. Graphical abstract: Image 1 Highlights: A new water-soluble fluorescent chemosensor PEGSB has been successfully developed. PEGSB exhibited highly selective and sensitive fluorescence response toward Al 3+ . Test papers coated with PEGSB were fabricated for on-site detection of Al 3+ in real water samples.